ANALYSIS OF FACTORS AFFECTING POST-POWER SYNDROME AND QUALITY OF LIFE IN THE ELDERLY - Retno Indarwati; Nursalam Nursalam; Rachmat Hargono; Suprajitno Suprajitno; Joni Haryanto; Rista Fauziningtyas; Randy Yusuf Pratama (Belitung Raya Foundation, Indonesia, 2017)
Background: Quality of life is the individuals’ perception of their place in life in the context of the cultural system and values in which they live, along with their goals, expectations, and worries. Retirement is an adaptable period that results in a change of role, changes in social interactions, and limited financial resources. Aim: This study aims to analyze the factors that affect post power syndrome and quality of life of the elderly. Methods: The design of this research was a correlation study with a cross-sectional approach. The population consisted of 44 retired elderly individuals. Purposive sampling was applied to the determined sample size. The independent variables were physiological stressors, psychological stressors and aging attitudes. The dependent variables were post-power syndrome and the quality of life of elderly people. The data were analyzed using Structural Equation Modeling- Partial Least Square (SEM-PLS) with a significance t statistic ≥ 1.96. Results: The findings showed all of the significant indicators measured to the variable factor. Physical stressor factors affect post-power syndrome with a t value of 2.366, and psychological stress factors affect post-power syndrome with a t value of 3.326. Aging behavior factors affects post-power syndrome with a t statistic of 5.296 and the post-power syndrome effect on the quality of life of the elderly has a t value of 7.689. Conclusion: There were significant effects in relation to physiological stressor factors, psychological stress factors, and aging attitudes towards post-power syndrome. There was an influence of post-power syndrome on the quality of elderly life.